2005
DOI: 10.1038/nchembio723
|View full text |Cite|
|
Sign up to set email alerts
|

Small-molecule interaction with a five-guanine-tract G-quadruplex structure from the human MYC promoter

Abstract: It has been widely accepted that DNA can adopt other biologically relevant structures beside the Watson-Crick double helix. One recent important example is the guanine-quadruplex (Gquadruplex) structure formed by guanine tracts found in the MYC (or c-myc) promoter region, which regulates the transcription of the MYC oncogene. Stabilization of this G-quadruplex by ligands, such as the cationic porphyrin TMPyP4, decreases the transcriptional level of MYC. Here, we report the first structure of a DNA fragment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
571
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 492 publications
(589 citation statements)
references
References 43 publications
17
571
1
Order By: Relevance
“…22 The present study has shown that this is not the case. The structure contains two single-residue double-chainreversal loops spanning three G-tetrad layers, a robust type of loop reported previously 15,28 that could play an important role in the folds of many G-quadruplexes 29 in K + solution. This quadruplex is remarkable in requiring the active participation of 18 out of the 22 nucleotides in the structural organization.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…22 The present study has shown that this is not the case. The structure contains two single-residue double-chainreversal loops spanning three G-tetrad layers, a robust type of loop reported previously 15,28 that could play an important role in the folds of many G-quadruplexes 29 in K + solution. This quadruplex is remarkable in requiring the active participation of 18 out of the 22 nucleotides in the structural organization.…”
Section: Discussionmentioning
confidence: 88%
“…We prepared samples (Table S1, Supporting Information) in which only one guanine was 2% 15 N-labeled at a time, using deliberately diluted 15 N-labeled phosphoramidite. 24 Guanine imino protons were unambiguously assigned by the site-specific low-enrichment approach 24 ( Figure 1b).…”
Section: Spectral Assignmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[97] Extensive substitution of the meso positions with groups other than pyridinium failed to generate compounds with improved activities, but the resulting structure-activity relationships demonstrated that base stacking and charge-charge interactions are important for porphyrin-DNA binding. [97] Subsequent X-ray crystallography and NMR studies have shown that TMPyP4 can bind to G-quadruplex DNA at many different positions, including the terminal G-tetrads, [98] and the loops, grooves, and phosphodiester backbone. [99] TMPyP4 has exhibited some promising anticancer activities in vivo, [62,100] but it has very poor DNA specificity, [86] causes anaphase bridges in sea urchin embryos, [87] and is highly toxic in vivo.…”
Section: Some Known G-quadruplex Ligands and Their Activitiesmentioning
confidence: 99%